Bank efficiency in Brazil: the importance for economic sustainability - Périco, Ana Elisa [UNESP]; Santana, Naja Brandão; Rebelatto, Daisy Aparecida do Nacimento (Inderscience Publishers, 2014)
Studies on efficiency achieved greater relevance in organisations within an open market framework, which in Brazil began around 1990. The objective of this paper, applying the data envelopment analysis methodology, is to analyse the efficiency of banks operating in the country using the database termed 'the biggest banks', periodically divulged by the Central Bank of Brazil in 2010-2012. The methodology was applied to the 26 largest banking organisations via two approaches, one was financial intermediation and the other was results. In the financial intermediation approach, the efficiency increase was the highest among banks specialised in credit from 2010 to 2012. Retail banks, especially the large ones, felt most intensely the reaction of 2011, a year considered as the sector's low performance year. In the results approach, the efficiency increase was higher among retail banks. Factors such as retractions in the SELIC rate and bank spreads impacted all banks, regardless of the segment.
Keywords: Bank competition; Retail ranks; Credit specialists; Financial intermediation; Bank results